Piezoelectric multilayer body and piezoelectric element
Patent Information
- Application Number
- JP2023149247
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2025-03-27
AI Technical Summary
【0016】 本開示の技術によれば、高い圧電性能かつ従来よりもさらに高い信頼性を有する圧電積層体及び圧電素子を提供することができる。
Smart Images

Figure 2025042311000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a piezoelectric laminate and a piezoelectric element. [Background technology]
[0002] Perovskite oxides such as lead zirconate titanate (Pb(Zr,Ti)O3, hereafter referred to as PZT) are known as materials with excellent piezoelectric and ferroelectric properties. Piezoelectrics made of perovskite oxides are used as piezoelectric films in piezoelectric elements that have a lower electrode, a piezoelectric film, and an upper electrode on a substrate. These piezoelectric elements are being deployed in a variety of devices, including memories, inkjet heads (actuators), micromirror devices, angular velocity sensors, gyro sensors, ultrasonic elements (PMUT: Piezoelectric Micromachined Ultrasonic Transducers), and vibration power generation devices.
[0003] It is described in Patent Documents 1 and 2 that a piezoelectric film with high orientation and good piezoelectric performance can be realized by adding Nb (niobium) to the B site in a PZT-based perovskite oxide. Patent Document 3 discloses that the piezoelectric performance of a piezoelectric film produced by a sol-gel method can be improved by adding Mn (manganese) in addition to Nb.
[0004] Patent Document 1 describes that in a piezoelectric film made of Nb-doped PZT, the crystal grain size has a wide distribution, and the piezoelectric performance can be improved by mixing crystals with large grain size and crystals with small grain size. Specifically, it describes that it is preferable that 20% or more of the crystal grains have a grain size of 100 nm or less, and 5% or more of the crystal grains have a grain size of 500 nm or more. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2009-71295 A [Patent Document 2] JP 2014-60330 A [Patent Document 3] International Publication No. 2015 / 146607 Summary of the Invention [Problem to be solved by the invention]
[0006] On the other hand, it is known to provide a seed layer between the piezoelectric film and the lower electrode in order to improve the piezoelectric performance. However, Patent Document 1 does not fully consider the case where a seed layer is provided.
[0007] The technology disclosed herein has been made in consideration of the above circumstances, and aims to provide a piezoelectric laminate and piezoelectric element that, when provided with a seed layer, have high piezoelectric performance and even higher reliability than conventional piezoelectric laminates and piezoelectric elements. [Means for solving the problem]
[0008] The piezoelectric laminate of the present disclosure is a piezoelectric laminate including a lower electrode layer, a seed layer, and a piezoelectric film in this order on a substrate, The piezoelectric film is mainly composed of a first perovskite oxide containing Pb, Zr, Ti, and Nb, the seed layer is mainly composed of a second perovskite oxide that is lattice-matched to the first perovskite oxide; The piezoelectric film has a crystal grain size distribution obtained by electron backscatter diffraction method, in which the proportion of crystal grains with a grain size of 100 nm or less is 15% or less, and the positive coercive electric field in the polarization-electric field characteristic is Ec + , the negative coercive field is Ec - In this case, |Ec + +Ec - |<|Ec + -Ec - | 55kV / cm≦Ec + ≦75kV / cm 75kV / cm≦Ec + -Ec - ≦100kV / cm Meet the following.
[0009] The piezoelectric film is preferably a sputtered film.
[0010] It is preferable that the percentage of crystal grains having a grain size of 100 nm or less is 10% or less.
[0011] The first perovskite oxide is Pb a {(Zr x Ti 1-x ) 1-y Nb y}O3 0 <x<1、0.08≦y≦0.15、0.9≦a≦1.2 It is preferable that the following is satisfied.
[0012] The seed layer is preferably electrically conductive.
[0013] The second perovskite oxide preferably has a lattice constant of 0.39 nm to 0.405 nm when considered as a pseudo cubic crystal.
[0014] The second perovskite oxide is preferably SrRuO3 or BaRuO3.
[0015] The piezoelectric element of the present disclosure includes the piezoelectric laminate of the present disclosure and an upper electrode layer provided on the piezoelectric film of the piezoelectric laminate. Effect of the Invention
[0016] According to the technique of the present disclosure, it is possible to provide a piezoelectric laminate and a piezoelectric element having high piezoelectric performance and higher reliability than ever before. [Brief description of the drawings]
[0017] [Figure 1] 1 is a schematic cross-sectional view showing a layer structure of a piezoelectric laminate and a piezoelectric element according to an embodiment. [Diagram 2]1 is a schematic diagram of a polarization-electric field (PE) hysteresis curve showing the PE characteristics of a piezoelectric element according to one embodiment. FIG. [Diagram 3] 1 shows PE hysteresis curves of Example 1 and Comparative Example 1. [Figure 4] 1 is an image pattern of crystal grains on the surface of the piezoelectric film of Example 1 obtained by the EBSD method. [Diagram 5] 1 shows the grain size distribution in the piezoelectric film of Example 1 obtained by EBSD. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, the embodiments of the present invention will be described with reference to the drawings. In the following drawings, the layer thicknesses and their ratios of each layer are appropriately changed for ease of visibility, and do not necessarily reflect the actual layer thicknesses and ratios. In this specification, a numerical range expressed using "~" means a range including the numerical values described before and after "~" as the lower and upper limits. In the numerical ranges described in stages in this disclosure, the upper or lower limit described in a certain numerical range may be replaced with the upper or lower limit of another numerical range described in stages. In addition, in the numerical ranges described in this disclosure, the upper or lower limit described in a certain numerical range may be replaced with a value shown in the examples.
[0019] Fig. 1 is a cross-sectional schematic diagram showing the layer structure of a piezoelectric stack 5 according to one embodiment and a piezoelectric element 1 including the piezoelectric stack 5. As shown in Fig. 1, the piezoelectric element 1 includes a piezoelectric stack 5 and an upper electrode layer 18. The piezoelectric stack 5 includes a substrate 10, and a lower electrode layer 12, a seed layer 13, and a piezoelectric film 15, which are laminated in this order on the substrate 10. Here, "lower" and "upper" do not mean up and down in the vertical direction, but simply refer to the electrode disposed on the substrate 10 side across the piezoelectric film 15 as the lower electrode layer 12, and the electrode disposed on the opposite side of the piezoelectric film 15 to the substrate 10 as the upper electrode layer 18.
[0020] The substrate 10 is not particularly limited, and examples thereof include substrates of silicon, glass, stainless steel, yttrium-stabilized zirconia, alumina, sapphire, silicon carbide, etc. The substrate 10 may be a laminate substrate such as a silicon substrate with a thermally oxidized film in which a SiO2 oxide film is formed on the surface of a silicon substrate. The substrate 10 may also be a resin substrate such as PET (polyethylene terephthalate), PEN (polyethylene naphthalate), polyimide, etc.
[0021] The lower electrode layer 12 is an electrode that is paired with the upper electrode layer 18 and applies a voltage to the piezoelectric film 15. The main component of the lower electrode layer 12 is not particularly limited, and examples thereof include metals or metal oxides such as Au (gold), Pt (platinum), Ir (iridium), Ru (ruthenium), Ti (titanium), Mo (molybdenum), Ta (tantalum), and Al (aluminum), as well as combinations thereof. ITO (indium tin oxide) may also be used. The lower electrode layer 12 may be a single layer or a multi-layer structure. When the lower electrode layer 12 has a multi-layer structure, it is also preferable to provide an adhesive layer such as Ti, TiW, or ZrO2 on the substrate 10 side in addition to the conductive layer made of the above material.
[0022] The thickness of the lower electrode layer 12 is not particularly limited, but is preferably about 50 nm to 300 nm, and more preferably 100 nm to 300 nm, overall.
[0023] The upper electrode layer 18 forms a pair with the lower electrode layer 12 and is an electrode for applying a voltage to the piezoelectric film 15. The main component of the upper electrode layer 18 is not particularly limited and includes metals such as Au, Pt, Ir, Ru, Ti, Mo, Ta, and Al, or metal oxides thereof, and combinations thereof. Further, ITO (Indium Tin Oxide), LaNiO3, SrRuO3, etc. may be used. The upper electrode layer 18 may be a single layer or may have a laminated structure composed of a plurality of layers. From the viewpoint of further suppressing oxygen diffusion from the piezoelectric film 15, at least the region of the upper electrode layer 18 in contact with the piezoelectric film 15 is preferably an oxide electrode.
[0024] The layer thickness of the upper electrode layer 18 is not particularly limited, and is preferably about 50 nm to 300 nm, more preferably 100 nm to 300 nm.
[0025] The piezoelectric film 15 is mainly composed of a first perovskite-type oxide containing Pb, Zr, Ti, and Nb. In this specification, the main component means a component occupying 80 mol% or more. The piezoelectric film 15 preferably has the first perovskite-type oxide occupying 90 mol% or more, and more preferably the piezoelectric film 15 is composed of 100 mol% of the first perovskite-type oxide (however, including inevitable impurities).
[0026] Nb-added PZT, which is a first perovskite-type oxide containing Pb, Zr, Ti, and Nb, is represented by the following general formula. Pb a {(Zr x Ti 1-x ) 1-y Nb y}O3 Here, it is preferably 0 < x < 1, 0 < y < 1, 0.9 ≦ a ≦ 1.2, and more preferably 0.08 ≦ y ≦ 0.15.
[0027] In addition, when the piezoelectric film 15 is formed as a sputtered film formed by a vapor phase growth method such as sputtering, a piezoelectric film having a very high piezoelectric constant can be obtained.
[0028] It is said that PZT-based perovskite oxides exhibit high piezoelectric properties at or near the morphotropic phase boundary (MPB). The MPB composition is when Zr:Ti (molar ratio) is close to 52:48, and in the above general formula, the MPB composition or its vicinity is preferable. "At or near the MPB" refers to a region where a phase transition occurs when an electric field is applied to the piezoelectric film. Specifically, the Zr:Ti (molar ratio) is preferably within the range of 45:55 to 55:45, that is, within the range of x = 0.45 to 0.55.
[0029] The thickness of the piezoelectric film 15 is preferably 0.2 μm or more and 5 μm or less, and more preferably 1 μm or more.
[0030] In the crystal grain size distribution of the piezoelectric film 15 obtained by the electron backscattered diffraction (EBSD) method, the proportion of crystal grains with a grain size of 100 nm or less is 15% or less. The proportion of crystal grains with a grain size of 100 nm or less is preferably 10% or less. The average grain size is preferably 200 nm or more, and more preferably 500 nm or more.
[0031] The seed layer 13 is mainly composed of a second perovskite oxide that is lattice-matched to the first perovskite oxide. The second perovskite oxide is a perovskite oxide having a different composition from the first perovskite oxide.
[0032] By providing the seed layer 13, it is possible to improve the crystallinity of the piezoelectric film 15 formed thereon. The piezoelectric film 15 formed on the seed layer 13 may be an epitaxial film that is epitaxially grown.
[0033] The second perovskite oxide preferably has a lattice constant of 0.39 nm to 0.405 nm when considered as a pseudocubic crystal. When the lattice constant is in this range, it is lattice-matched with the first perovskite oxide, which is Nb-doped PZT, and therefore the crystallinity of the piezoelectric film 15 formed thereon can be improved.
[0034] The seed layer 13 is preferably conductive. Here, being conductive means that the seed layer 13 has an electrical resistivity of such a degree that it can function as an electrode. Here, the electrical resistivity at 20° C. is 10 -5 A seed layer 13 having a conductivity of Ω·m or less can function as an electrode for applying a driving voltage to the piezoelectric film 15 together with the lower electrode layer 12 if the seed layer 13 is conductive.
[0035] Specific examples of the second perovskite oxide include SrRuO3, BaRuO3, and PbTiO3. These have a lattice constant of 0.39 nm to 0.405 nm when considered as a pseudocubic crystal. As the second perovskite oxide, SrRuO3 or BaRuO3, which is particularly conductive, is preferable.
[0036] FIG. 2 is a schematic diagram of a PE hysteresis curve showing the polarization-electric field (PE) characteristics obtained by applying a sweep voltage to the piezoelectric film 15 with the lower electrode layer 12 grounded and the upper electrode layer 18 used as a driving electrode. In the PE hysteresis curve, a positive voltage is shown when a positive potential is applied to the upper electrode layer 18, and a negative voltage is shown when a negative potential is applied to the upper electrode layer 18. The data may be unstable in the first cycle of measurement due to the influence of the polarization state before the measurement, but a stable curve that behaves approximately the same is obtained from the second cycle onwards. A stable PE hysteresis curve is used to evaluate the coercive electric field of the piezoelectric film. For example, data from the third cycle is used.
[0037] As shown in FIG. 2, the piezoelectric film 15 generates a positive coercive electric field Ec + , the negative coercive field is Ec - In this case, |Ec + +Ec - |<|Ec + -Ec - | 55kV / cm≦Ec + ≦75kV / cm 75kV / cm≦Ec + -Ec -≦100kV / cm Meet the following.
[0038] The coercive field is the field at which the polarization becomes zero in the PE hysteresis curve. As shown in Figure 2, there are two coercive fields in one hysteresis curve. The positive coercive field Ec + refers to the relatively positive coercive field (the right side in the figure) of the two coercive fields, and the negative coercive field Ec - refers to the coercive electric field on the relatively negative electric field side (left side in the figure).
[0039] In the PE hysteresis curve shown in Figure 2, the difference in the coercive field Ec + -Ec - The absolute value of indicates the width of the hysteresis. Half the sum of the coercive electric fields (Ec + +Ec - ) / 2 indicates the center of hysteresis H0. The shift of the center of hysteresis H0 from the origin indicates that the piezoelectric film 15 has spontaneous polarization. In addition, the shift of the center of hysteresis H0 toward the positive electric field side indicates that spontaneous polarization occurs in the direction opposite to the direction of the electric field when a positive voltage is applied.
[0040] |Ec + -Ec - | is the absolute value of the difference in the coercive electric field, and as mentioned above, it indicates the width of the hysteresis curve. Also, as mentioned above, the center of the hysteresis curve is (Ec + +Ec - ) / 2. Therefore, (Ec + +Ec - The absolute value of (x) / 2 indicates the amount of shift of the hysteresis curve. Above |Ec + +Ec - |<|Ec + -Ec - | The relation is: |Ec + +Ec - | / 2<|Ec + -Ec - | / 2 and means that the shift amount of the hysteresis curve is less than half the hysteresis width, that is, the hysteresis curve includes the origin.
[0041] In general, the spontaneous polarization of Nb-added PZT is upward in the film thickness direction from the substrate side immediately after film formation. Therefore, in a piezoelectric device having an Nb-added PZT film, it is common to drive the Nb-added PZT film by making the direction of the spontaneous polarization of the Nb-added PZT film coincide with the direction of the electric field. Therefore, in a conventional piezoelectric device having an Nb-added PZT film, it is common to use the upper electrode layer 18 as a drive electrode and perform negative voltage drive. However, as described above, the piezoelectric film 15 of this embodiment is an Nb-added PZT film, and the hysteresis curve includes the origin and has a large width. This means that it is possible to polarize in the opposite direction to the spontaneous polarization immediately after film formation. By polarizing in the opposite direction to the spontaneous polarization immediately after film formation, it is possible to perform positive voltage drive when the upper electrode layer 18 is used as the drive electrode. A positive voltage drive is cheaper than a negative voltage drive, which leads to cost reduction of the piezoelectric device.
[0042] As described above, the piezoelectric laminate 5 and the piezoelectric element 1 of this embodiment include a seed layer 13 mainly made of a second perovskite oxide between the piezoelectric film 15 mainly made of a first perovskite oxide containing Pb, Zr, Ti, and Nb and the lower electrode layer 12, and the piezoelectric film 15 has a ratio of crystal grains with a crystal grain size of 100 nm or less of 15% or less as obtained by electron backscatter diffraction. Also, the piezoelectric film 15 has a positive coercive electric field in the polarization-electric field characteristics of Ec + , the negative coercive field is Ec - The above relationship is satisfied when
[0043] The present inventors have found that such a configuration can improve the piezoelectric performance and reliability of the piezoelectric film (see Examples below). As mentioned above, |Ec + -Ec -| corresponds to the width of the hysteresis. The larger the hysteresis width, the more stable the piezoelectric film is, with less polarization reversal. On the other hand, |Ec + -Ec - If | is too large, it becomes difficult to align the polarization, and the piezoelectric performance decreases when the polarization is released. It is preferable that the coercive electric field is equal to or less than the driving voltage. The piezoelectric film 15 of this embodiment has a coercive electric field of 55 kV / cm≦Ec + ≦75kV / cm, 75kV / cm≦Ec + -Ec - ≦100kV / cm, so it is stable and highly reliable. In addition, because the hysteresis curve includes the origin, no polarization reversal occurs during operation, which reduces power consumption and leads to long-term reliability.
[0044] By providing the seed layer 13, the piezoelectric film 15 with good lattice matching grows, so that the stress applied to the piezoelectric film can be suppressed compared to the case where the seed layer 13 is not provided. By suppressing the stress of the piezoelectric film 15, the withstand voltage and durability can be improved, and high reliability can be obtained. In Patent Document 1, the seed layer 13 is not provided, and the piezoelectric film contains many crystal grains with small grain size, thereby alleviating the stress, but by providing the seed layer 13, the stress can be suppressed even without the inclusion of crystal grains with small grain size. The inventors have found that, conversely, when the seed layer 13 is provided, the piezoelectric performance and reliability can be improved by suppressing the crystal grains with small grain size of 100 nm or less. Dielectric breakdown often occurs at grain boundaries, and it is believed that suppressing the crystal grains with small grain size suppresses the number of grain boundaries, which leads to the improvement of the withstand voltage and durability.
[0045] The above-mentioned piezoelectric film 15 can be obtained by, when forming a film on the seed layer 13 by sputtering, stopping the film formation at a very thin film formation stage in the early stage of film formation, specifically at a film thickness of 100 nm or less, performing an annealing treatment at a high temperature of 600°C to 700°C, and then continuing the film formation to a set film thickness (for example, 2 μm). It is believed that the annealing treatment promotes the crystal growth of the Nb-doped PZT, and reduces the number of small crystal grains.
[0046] The piezoelectric element 1 or the piezoelectric laminate 5 in each of the above embodiments can be applied to ultrasonic devices, mirror devices, sensors, memories, and the like. EXAMPLES
[0047] Specific examples and comparative examples of the piezoelectric element of the present disclosure will be described below. First, a method for producing the piezoelectric element of each example will be described. A sputtering device was used to deposit each layer. The explanation of the production method will be given with reference to the reference numerals of each layer of the piezoelectric element 1 shown in FIG.
[0048] (Production method) As the substrate 10, a silicon substrate with a thermal oxide film was used.
[0049] A substrate with an electrode layer was prepared in which an adhesion layer made of Ti with a thickness of 20 nm, a lower electrode layer 12 made of Ir with a thickness of 150 nm, and a seed layer 13 made of SrRuO3 (SRO in Table 1) with a thickness of 20 nm were sequentially laminated on a thermal oxide film of a substrate 10. Note that, for Comparative Examples 1 and 3, a substrate with an electrode layer was prepared in which an adhesion layer made of Ti with a thickness of 20 nm and a lower electrode layer 12 made of Ir with a thickness of 150 nm were sequentially laminated on a thermal oxide film of a substrate 10 without a seed layer.
[0050] <Piezoelectric film> On the seed layer 13, a Nb-added PZT film was formed as the piezoelectric film 15 under the following sputtering conditions. The film formation was temporarily stopped at an early stage of film formation, and an annealing treatment was performed, and finally, a 2 μm-thick Nb-added PZT film was formed. A Nb-added PZT target was used for film formation. The Pb composition ratio was 1.3, and the Zr / Ti molar ratio was an MPB composition (Zr / Ti=52 / 48), that is, a target with x=0.52 and Nb composition ratio y=0.12 was used. The substrate temperature during film formation was set to 550°C.
[0051] -Sputtering conditions for piezoelectric film- Target-substrate distance: 100mm Target input power: 3kW Degree of vacuum (film formation pressure): 0.5Pa Atmosphere: Ar / O2 mixture (O2 volume fraction 2.5%) Substrate temperature setting: 550℃ Substrate bias voltage: +40V
[0052] - Annealing conditions - The conditions for annealing the film after stopping the film formation are as listed in Table 1. For example, in the case of Example 1, an Nb-added PZT film was formed to a thickness of 30 nm as the initial piezoelectric film, and then annealing was performed at a temperature of 650°C for 10 minutes. The annealing was performed in a state where the film formation was stopped in the film formation device and only the temperature was increased in a vacuum. Also, in the cases of Comparative Examples 1 and 2, the film formation was not stopped midway, i.e., the annealing was not performed, and a 2 μm piezoelectric film was formed as it was.
[0053] <Top electrode layer> An ITO layer having a thickness of 100 nm was formed as an upper electrode layer 18 on the piezoelectric film 15 of the above-mentioned laminated substrate by sputtering.
[0054] <Formation of electrode pattern for evaluation> Before forming the upper electrode layer 18, a resist pattern was formed by photolithography, the upper electrode layer 18 was formed on the resist pattern, and an upper electrode pattern for evaluation was formed by lift-off.
[0055] The laminates of the comparative examples and the examples were produced by the above steps. Table 1 shows the seed layer, the piezoelectric film thickness before annealing (initial piezoelectric film thickness), and the temperature and time of the annealing for each comparative example and example.
[0056] [Table 1]
[0057] (Preparation of evaluation samples) -Evaluation sample 1- A rectangular piece measuring 2 mm×25 mm was cut out from the laminate to prepare a cantilever as evaluation sample 1.
[0058] -Evaluation sample 2- A 25 mm×25 mm portion having upper electrode layer 18 patterned in a circle with a diameter of 400 μm at the center of the surface of piezoelectric film 15 was cut out from the laminate to provide evaluation sample 2.
[0059] <Measurement of polarization-electric field characteristics> For the piezoelectric elements of each Example and Comparative Example, the polarization-electric field (PE) hysteresis curve was measured using the evaluation sample 2. A ferroelectric property evaluation system FEC10 manufactured by Toyo Corporation was used for the measurement. For the piezoelectric elements of each Example and Comparative Example, the lower electrode layer 12 was grounded, and the driving voltage applied to the upper electrode layer 18 was changed from 0V to +40V to -40V to 0V with a triangular wave of 10Hz, and the change in the polarization value at that time was obtained. In addition, the measurement of the hysteresis curve was set to a change of 0V to +40V to -40V to 0V as one cycle, and the coercive electric field value was determined from the data of the third cycle. As already mentioned, in the measurement of the hysteresis curve, the first cycle is unstable, and the hysteresis is generally stable from the second cycle onwards and approximately the same hysteresis is obtained. Here, the data of the third cycle was used just to be sure. FIG. 3 shows the PE hysteresis curves of Example 1 and Comparative Example 1. The horizontal axis is the electric field calculated by dividing the applied voltage by the thickness of 2 μm.
[0060] As shown in FIG. 3, in the hysteresis curve of Example 1, the positive coercive field Ec + is 66kV / cm, negative coercive field Ec - was -27kV / cm. Therefore, |Ec + +Ec - | is 39 kV / cm, and |Ec + -Ec - The coercive electric field for each of the other Examples and Comparative Examples is as shown in Table 2.
[0061] <Measurement of piezoelectric constant> Using a cantilever, the piezoelectric constant d was measured by applying a sine wave voltage of +10V±10V, i.e., a bias voltage of +10V plus a sine wave with an amplitude of 10V, according to the method described in I. Kanno et. al. Sensor and Actuator A 107(2003)68. 31 [pm / V] was measured. Note that, before measuring the piezoelectric constant, a voltage of +40 V was applied for 10 seconds to perform a poling process. The measurement results are shown in Table 2.
[0062] The piezoelectric constant was evaluated according to the following criteria, and the evaluation results are shown in Table 2. A:200pm / V or more B: 170pm / V or more, less than 200pm / V C: Less than 170pm / V
[0063] <Evaluation of withstand voltage> The withstand voltage (breakdown voltage) of each of the examples and comparative examples was measured. Using evaluation sample 2, the lower electrode layer 12 was grounded, and a positive voltage was applied to the upper electrode layer 18 at a rate of change of +1 V / sec. The voltage at which a current of 1 mA or more flowed was regarded as the withstand voltage. Ten samples were prepared for each example, and measurements were performed a total of 10 times. The average value is shown in Table 2 as the withstand voltage [V].
[0064] The withstand voltage was evaluated according to the following criteria, and the evaluation results are shown in Table 2. A:150V or more B: 100V or more, less than 150V C: Less than 100V
[0065] <Evaluation of driving stability (reliability)> A time dependent dielectric breakdown (TDDB) test was conducted to evaluate the driving stability of each of the examples and comparative examples. Using evaluation sample 2, the lower electrode layer 12 was grounded and a voltage of +40V was applied to the upper electrode layer 18 in an environment of 120°C, and the time (hr) from the start of voltage application until dielectric breakdown occurred was measured. The measurement results are shown in Table 2. The TDDB test was conducted for 2000 hours, and those that did not experience dielectric breakdown up to 2000 hours are listed as 2000 in Table 2.
[0066] Reliability was evaluated according to the following criteria, and the evaluation results are shown in Table 2. A:1500hr or more B: 1000hrs or more, less than 1500hrs C: Less than 1000 hours
[0067] <Method of measuring crystal grain size> The surface of the piezoelectric film after deposition, i.e., the surface of the piezoelectric film before deposition of the upper electrode, was measured by EBSD. As the measuring device, a scanning electron microscope (SEM) JSM-7001F manufactured by JEOL Ltd. and an OIM manufactured by EBSD TSL Ltd. were used. The image pattern of the crystal grains on the surface of the piezoelectric film for Example 1 obtained by the EBSD method is shown in FIG. 4. As shown in the enlarged view in FIG. 4, the crystal grains were identified, and the diameter of the smallest circumscribed circle was obtained as the crystal grain size. FIG. 5 shows the grain size distribution obtained from FIG. 4. In FIG. 5, on the horizontal axis, ~0.1 indicates 0.1 μm or less (100 nm or less), ~0.2 indicates more than 0.1 μm and less than 0.2 μm, and ~0.3 indicates more than 0.2 μm and less than 0.3 μm. The same applies to ~0.4 and onwards. As shown in FIG. 5, in Example 1, the crystal grains with a grain size of 100 nm or less were 10% of the total number of crystal grains within the field of view. The ratio of crystal grains with a grain size of 100 nm or less for each Example and Comparative Example was as shown in Table 2.
[0068] In addition, in Table 2, the lowest evaluation result among the evaluations of the piezoelectric constant, the withstand voltage, and the reliability for each of the examples and comparative examples is shown as an overall evaluation. [Table 2]
[0069] The results of Comparative Examples 1 and 3 showed that, in the absence of a seed layer, Comparative Example 1, in which the proportion of crystal grains with a grain size of 100 nm or less exceeded 30%, had higher piezoelectric constant, withstand voltage, and reliability.
[0070] Examples 1 to 5 were rated B or higher in all evaluations, and good results were obtained in all of the piezoelectric constant, withstand voltage, and reliability. Examples 1 to 5 and Comparative Example 2 satisfied the following. Comparative Example 1 and Comparative Example 3 did not satisfy at least one of the following formulas. |Ec + +Ec - |<|Ec + -Ec - | 55kV / cm≦Ec + ≦75kV / cm 75kV / cm≦Ec + -Ec - ≦100kV / cm Moreover, the ratio of crystal grains having a grain size of 100 nm or less was 15% or less in Examples 1 to 5. It was clear that by satisfying these ranges, good piezoelectric constant, withstand voltage, and reliability could be obtained.
[0071] Example 3 was evaluated as having low withstand voltage and reliability compared to Examples 1, 2, 4, and 5. From this result, it is considered that it is more preferable that the proportion of crystal grains with a grain size of 100 nm or less in the piezoelectric film 15 is 10% or less. Furthermore, in the case where a seed layer is provided, Comparative Example 2, in which the proportion of crystal grains with a grain size of 100 nm or less is high at 35%, had a good piezoelectric constant, but low withstand voltage and reliability compared to Examples 1 to 5, making clear the effect of reducing the proportion of crystal grains with a grain size of 100 nm or less.
[0072] All publications, patent applications, and standards mentioned in this specification are herein incorporated by reference to the same extent as if each individual publication, patent application, or standard was specifically and individually indicated to be incorporated by reference.
[0073] The following supplementary notes are further disclosed regarding the above embodiment. <Appendix 1> A piezoelectric laminate including a lower electrode layer, a seed layer, and a piezoelectric film in this order on a substrate, The piezoelectric film is mainly composed of a first perovskite oxide containing Pb, Zr, Ti, and Nb, the seed layer is mainly composed of a second perovskite oxide that is lattice-matched to the first perovskite oxide; The piezoelectric film has a crystal grain size distribution obtained by electron backscatter diffraction method, in which the proportion of crystal grains with a grain size of 100 nm or less is 15% or less, and a positive coercive electric field in the polarization-electric field characteristic is Ec + , the negative coercive field is Ec - In this case, |Ec + +Ec - |<|Ec + -Ec - | 55kV / cm≦Ec + ≦75kV / cm 75kV / cm≦Ec + -Ec - ≦100kV / cm A piezoelectric laminate that satisfies the above requirements. <Appendix 2> 2. The piezoelectric stack according to claim 1, wherein the piezoelectric film is a sputtered film. <Appendix 3> 3. The piezoelectric stack according to claim 1, wherein the crystal grains having a grain size of 100 nm or less account for 10% or less. <Appendix 4> The first perovskite oxide is Pb a {(Zr x Ti 1-x ) 1-y Nb y}O3 0 <x<1、0.08≦y≦0.15、0.9≦a≦1.2 4. The piezoelectric laminate according to claim 1, wherein <Appendix 5> 5. The piezoelectric stack of claim 1, wherein the seed layer is electrically conductive. <Appendix 6> 6. The piezoelectric stack according to claim 1, wherein the second perovskite oxide has a lattice constant of 0.39 nm to 0.405 nm when considered as a pseudo cubic crystal. <Appendix 7> 7. The piezoelectric stack according to claim 1, wherein the second perovskite oxide is SrRuO3 or BaRuO3. <Appendix 8> A piezoelectric laminate according to any one of claims 1 to 7; an upper electrode layer provided on the piezoelectric film of the piezoelectric laminate. [Explanation of symbols]
[0074] 1 Piezoelectric element 5 Piezoelectric laminate 10 Substrate 12 Lower electrode layer 13 Seed layer 15 Piezoelectric film 18 Upper electrode layer
Claims
1. A piezoelectric laminate including a lower electrode layer, a seed layer, and a piezoelectric film in this order on a substrate, the piezoelectric film is mainly composed of a first perovskite oxide containing Pb, Zr, Ti, and Nb; the seed layer is mainly composed of a second perovskite oxide that is lattice-matched to the first perovskite oxide; The piezoelectric film has a crystal grain size distribution obtained by electron backscatter diffraction method, in which the proportion of crystal grains with a grain size of 100 nm or less is 15% or less, and a positive coercive electric field in the polarization-electric field characteristic is Ec + , the negative coercive field is Ec - In this case, |Ec + +Ec - |<|Ec + -Ec - | 55kV / cm≦Ec + ≦75kV / cm 75kV / cm≦Ec + -Ec - ≦100kV / cm A piezoelectric laminate that satisfies the above requirements.
2. The piezoelectric stack according to claim 1 , wherein the piezoelectric film is a sputtered film.
3. 3. The piezoelectric stack according to claim 1, wherein the crystal grains having a grain size of 100 nm or less account for 10% or less of the total crystal grains.
4. The first perovskite oxide is Pb a {(Cr x Today 1-x ) 1-y N﹂ y }O 3 0<x<1, 0.08≦y≦0.15, 0.9≦a≦1.2 The piezoelectric laminate according to claim 1 or 2, which satisfies the above.
5. The piezoelectric stack of claim 1 or 2, wherein the seed layer is electrically conductive.
6. 3. The piezoelectric stack according to claim 1, wherein the second perovskite oxide has a lattice constant of 0.39 nm to 0.405 nm when considered as a pseudo cubic crystal.
7. The second perovskite oxide is SrRuO 3 or BaRuO 3 3. The piezoelectric laminate according to claim 1 or 2,
8. The piezoelectric laminate according to claim 1 or 2; an upper electrode layer provided on the piezoelectric film of the piezoelectric laminate.
Citation Information
Patent Citations
Piezoelectric device and liquid discharge apparatus using the same
JP2009071295A
Piezoelectric device and using method thereof
JP2014060330A
Composition for forming manganese- and niobium-doped PZT piezoelectric film
WO2015146607A1